AKTIVIITAS ANTIOKSIDAN ANTIHIPERLIPIDEMIA DAN ANTIHIPERTENSI DARI EKSTRAK ETANOL DAUN KEDABU (Sonneratia ovata. Backer) - Raharjo, Danang; Fitriawati, Anna; Aminnulloh, Muhhamad (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Kedabu (Sonneratia ovata. Backer) is one type of mangrove from the genus Sonneratia with high flavonoid content that has the potential as an antioxidant. The flavonoid content in the kedabu plant includes sonnerphenolic, vanillin, (-)-(R)-nyasol, (-)-(R)-4’-O-methylnyasol, maslinic acid, lingueresinol and gallic acid. Flavonoids as antioxidants can improve blood lipid profiles by lowering total cholesterol, triglycerides, and LDL, and increasing HDL. In addition, flavonoids can inhibit the activity of Angiotensin-converting enzyme (ACE) so that it has the potential as an antihypertensive. This study aims to examine the potential of kedabu leaf extract as an antioxidant, antihypertensive and antihyperlipidemic agent tested in vitro. Antioxidant testing was carried out using the ABTS (2,2-azinobis-3-ethylbenzothiazoline-6sulfonate) method, antihypertension testing was carried out by inhibiting Angiotensin converting enzyme and antihyperlipidemia testing was carried out by inhibiting the lipase enzyme. The results of the study showed that the total flavonoid content was 38.248 ± 0.142 mgQE / g with an antioxidant capacity with an IC50 value of 28.30 ± 0.558 ppm. From the Angiotensin converting enzyme inhibition and lipase enzyme inhibition tests, the IC50 values ​​were 44.851 ± 0.130 ppm and 39.133 ± 0.889 ppm, respectively. Based on these results, the kedabu leaf extract showed antihypertensive and antihyperlipidemia activities by inhibiting the activity of Angiotensin converting enzyme and lipase enzymes.